Improving Students' Ability to Memorize the Quran: What Strategies Should Teachers Use? - Abdullah, Mahmoud; Oktavia, Gifa; Almasi, Mustapha (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2024)
Memorizing the Quran is a noble act that is loved by Allah SWT. This is because memorizing the Quran means that a person is trying to preserve the purity of the Quran. This cannot be separated from the efforts of a teacher in guiding their students to always memorize the Quran from an early age. It is the teacher's hard work that determines a student's success in memorizing the Quran. This study aims to analyze the strategies used by tahfizh teachers in improving their students' ability to memorize the Quran. This study uses a qualitative method with a phenomenological approach. The subjects of this study are tahfizh teachers and students. Data collection used observation, interviews, and documentation methods. All interview results were analyzed thematically using the Miles & Hubberman Interactive Model Analysis technique, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the data analysis found that there were six strategies used by teachers to improve students' ability to memorize the Quran, namely: i) using various methods, such as talaqqi, tasmi', and takriri, ii) applying the ODOA (one day one ayat) method, iii) guiding students to routinely perform muraja'ah, iv) constantly motivating students to improve their Quran memorization, v) giving memorization assignments and punishments to students, vi) teachers correcting students' recitation. The results of this study can be used as preliminary data for subsequent researchers examining this issue in different contexts and issues.